Visual organizer facilitates the conceptualization in cooperative learning of first cycles students - Flores Galarreta, Patricia Noelia (2020)
This descriptive research, worked under the four phases of the design of an action research, uses the qualitative technique of direct observation and as an instrument the checklist. It contributes to improve classroom learning practice in the creation of the concept, in the face of confusion of ideas due to lack of understanding of the objective and diversity. The population intervened are the first cycle students of a section of the Creativity course of an institute. Cooperative learning and the visual organizer tool were used together with the visual and auditory learning style. The unintervened population; another section of the same course worked cooperatively with a concept generation technique. It concludes; In the section that used the co-instructional tool, he facilitated the understanding of the objective and the creation of the concept, culminating his academic work satisfactorily, unlike the unintervened section.